the IMPLEMENTASI PENDEKATAN KONSTEKTUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA: Indonesia - Gilang Medal Pangrestu; Dicky Kurnia; Feriska Br Napitupulu; Aminah; Tengku Rio Akbar; Julinda Siregar (STKIP Subang, 2025)
Science learning in elementary schools often shows low conceptual understanding and limited student engagement because instruction is mainly teacher-centered and rarely connected to real-life contexts. This study aims to determine the effect of implementing the Contextual Teaching and Learning (CTL) approach on students’ science learning outcomes. The research employed a quasi-experimental method using a one-group pretest–posttest design involving 30 fifth-grade students. Data were collected through pretest and posttest instruments based on science competency indicators. The results indicate a significant improvement in students’ scores after the CTL implementation, as reflected in the higher posttest average. These findings suggest that CTL helps students build more meaningful scientific understanding and enhances their participation during learning activities.